Orthodontic bonding procedures significantly influence biofilm composition - Da-Mi Jeon; Jung-Sub An; Bum-Soon Lim; Sug-Joon Ahn (SpringerOpen, 2020)
Abstract Background Because changes in surface properties affect bacterial adhesion, orthodontic bonding procedures may significantly influence biofilm formation and composition around orthodontic appliances. However, most studies used a mono-species biofilm model under static conditions, which does not simulate the intraoral environment and complex interactions of oral microflora because the oral cavity is a diverse and changeable environment. In this study, a multi-species biofilm model was used under dynamic culture conditions to assess the effects of the orthodontic bonding procedure on biofilm formation and compositional changes in two main oral pathogens, Streptococcus mutans and Porphyromonas gingivalis. Methods Four specimens were prepared with bovine incisors and bonding adhesive: untreated enamel surface (BI), enamel surface etched with 37% phosphoric acid (ET), primed enamel surface after etching (PR), and adhesive surface (AD). Surface roughness (SR), surface wettability (SW), and surface texture were evaluated. A multi-species biofilm was developed on each surface and adhesion amounts of Streptococcus mutans, Porphyromonas gingivalis, and total bacteria were analyzed at day 1 and day 4 using real-time polymerase chain reaction. After determining the differences in biofilm formation, SR, and SW between the four surfaces, relationships between bacteria levels and surface properties were analyzed. Results The order of SR was AD < PR < BI < ET, as BI and ET showed more irregular surface texture than PR and AD. For SW, ET had the greatest value followed by PR, BI, and AD. S. mutans and P. gingivalis showed greater adhesion to BI and ET with rougher and more wettable surfaces than to AD with smoother and less wettable surfaces. The adhesion of total bacteria and S. mutans significantly increased over time, but the amount of P. gingivalis decreased. The adhesion amounts of all bacteria were positively correlated with SR and SW, irrespective of incubation time. Conclusions Within the limitations of this study, changes in SR and SW associated with orthodontic bonding had significant effects on biofilm formation and composition of S. mutans and P. gingivalis.